(untitled) (Altre Modernità, 2010)
Once the dystopian genre gained its actual shape in literature, during the first decades of the twentieth century several concepts appeared constantly in most of this kind of novels. A common topic has been the dissidence of the main character, who at the initial stage of the plot is a strong supporter of the ideals of the state he/she lives in. Hence, such kind of power, at first caring and protective, turns into a pursuing machine with the aim of eradicating any alternative thinking. Furthermore, since the fifties, films based on this literary genre have also adapted the evolution from love to hate towards the totalitarian state, that must bring the new dissident back under the protection of power. My purpose in this essay is to show some instances of this change in dystopian literature and cinema along different periods of the twentieth and twenty-first centuries, in order to prove that the idea is still worth studying, as writers and directors have kept it as an important axis of the plot.